Students’ Voices Towards Online Debate Through WhatsApp as Alternative Media to Enhance Critical Thinking Skills During Covid-19 Pandemic - Pahmi, Pahmi; Niah, Siti (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study aims to find out students’ voices towards online debate through WhatsApp as alternative media to enhance critical thinking skills during Covid-19 pandemic. Sixteen undergraduate students participated in online debate for ten sessions throughout one whole semester. At the end of the research, eight students volunteered to participate in semi-structured interviews. The interviews were conducted to find out the participants’ voices about the online debate. The research findings reveal the participants believe that critical thinking skills are important to be mastered. Furthermore, the respondents believe that the online debate is good learning media to help them improve their critical thinking skills during this Covid-19 pandemic. The activity provides flexibility in terms of time and place. Other advantages, as claimed by the participants, include reducing students’ anxiety, improving teamwork skills, and improving persuasion skills. However, some barriers were also found based on the participants’ responses. The participants are concerned with the issue of being distracted, tendency to copy and paste, unstable network, and limited time.